Synthesis of Base-Modified dNTPs Through Cross-Coupling Reactions and Their Polymerase Incorporation to DNA - Ménová, Petra; Cahová, Hana; Vrábel, Milan; Hocek, Michal (Methods in molecular biology (Clifton, N.J.), 2019)
Synthesis of base-modified dNTPs through the Suzuki or Sonogashira cross-coupling reactions of halogenated dNTPs with boronic acids or alkynes is reported, as well as the use of these modified dNTPs in polymerase incorporations to oligonucleotides or DNA by primer extension or PCR.
Keywords: DNA-Directed DNA Polymerase; Halogenation; Modified DNA; Enzymatic synthesis; DNA; Nucleotides; Nucleoside triphosphates; DNA-dependentní DNA-polymerasy; DNA polymerases; halogenace; nukleotidy